Alphaworld: bird families - Woolley, Marilyn (Horwitz Education St. Leonards, N.S.W., 2004)
"Bird Families" is a delightful exploration of various avian species and their unique familial structures. The narrative dives into the lives of different bird families, showcasing the strong pair bonds of lovebirds, the dedicated parenting of penguins in harsh climates, and the elegant partnerships of swans, which illustrate deep connections that often last a lifetime. Through these captivating stories, the work celebrates the diversity of avian life while providing an educational journey into the fascinating behaviors and adaptations of birds as they nurture and protect their young.